2024
DOI: 10.3390/jpm14010122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intradermal Therapy (Mesotherapy) on Bilateral Cervicobrachial Pain

Maurizio Ranieri,
Riccardo Marvulli,
Eleonora D’Alesio
et al.

Abstract: Background: Mesotherapy is a procedure or a process of injecting drugs into the skin. This technique can help decrease the total drug dose due to its drug-sparing effect on the systemic route and can be utilized to treat nonspecific neck pain that occurs in the lateral and posterior neck. Methods: Ten patients with bilateral cervicobrachial pain were recruited and evaluated at T0 before treatments, T1 at the end of the treatment (42 days after T0), and T2 (72 days after T0). Assessments consisted of performing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Another study published in January 2024 by Ranieri et al [ 27 ] reported on the use of mesotherapy for cervicobrachial pain syndrome with bilateral radiating to the arms/shoulders. This study found that mesotherapy with diclofenac sodium reduced pain intensity and improved functional outcomes, with no significant side effects in patients with myofascial pain syndrome located in the cervical/shoulder region.…”
Section: Discussionmentioning
confidence: 99%
“…Another study published in January 2024 by Ranieri et al [ 27 ] reported on the use of mesotherapy for cervicobrachial pain syndrome with bilateral radiating to the arms/shoulders. This study found that mesotherapy with diclofenac sodium reduced pain intensity and improved functional outcomes, with no significant side effects in patients with myofascial pain syndrome located in the cervical/shoulder region.…”
Section: Discussionmentioning
confidence: 99%
“…Using this equipment, the biomechanical feature of the BB is calculated as a numerical value considering the vibration reduced by the muscle . The accurateness of this measurement is well-documented in the literature [ 29 ].…”
Section: Case Reportmentioning
confidence: 99%
“…Analgesic mesotherapy is an outpatient treatment involving multiple mesodermal microinjections of active substances, administered through 27G 0.4 × 4 mm needles, at body parts affected by pain and functional limitation. This technique allows a small amount of drug to be used directly on the area to be treated, reducing systemic drug intake ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%